(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article describes the historical basis of the development of the worldview against harassment and aggression among female students, as well as the content of the work carried out to ensure the participation of women and girls in all stages of political, economic and social life.